2009
DOI: 10.3390/s90604615
|View full text |Cite
|
Sign up to set email alerts
|

A New and Inexpensive Pyranometer for the Visible Spectral Range

Abstract: This paper presents the design, construction and testing of a new photodiode-based pyranometer for the visible spectral range (approx. 400 to 750 nm), whose principal characteristics are: accuracy, ease of connection, immunity to noise, remote programming and operation, interior temperature regulation, cosine error minimisation and all this at a very low cost, tens of times lower than that of commercial thermopile-based devices. This new photodiode-based pyranometer overcomes traditional problems in this type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 23 publications
0
38
0
1
Order By: Relevance
“…The negative bias (Figure 4) indicated that the portable system values were higher on average than those at AmeriFlux sites. Possible explanations for this bias are sensor degradation [ Feuermann and Zemel , 1993; Martínez et al , 2009], sensor out‐of‐calibration, or dirty sensor.…”
Section: Resultsmentioning
confidence: 99%
“…The negative bias (Figure 4) indicated that the portable system values were higher on average than those at AmeriFlux sites. Possible explanations for this bias are sensor degradation [ Feuermann and Zemel , 1993; Martínez et al , 2009], sensor out‐of‐calibration, or dirty sensor.…”
Section: Resultsmentioning
confidence: 99%
“…This logic is the basis for the development of an open source colorimeter [17], an open source control system for a solar plant [18], and a new and inexpensive pyranometer [19]. These are only some example of research instruments developed following the DIY approach that have been shared, in line with the maker movement philosophy.…”
Section: Introductionmentioning
confidence: 99%
“…We used polytetrafluoroethylene (TeflonTM) as a cosine corrector, to minimize the effects of incidence angle on observation accuracy. Its optical properties remain constant over a wide range of wavelengths, from UV up to near-infrared, and it is widely used for radiation sensor cosine correction [28][29][30]. Light transmitted through the diffuser radiates, according to Lambert's cosine law.…”
Section: Dome and Cosine Correctormentioning
confidence: 99%
“…The silicon photoelectric detector is temperature-dependent [41]: the output increases as the device's temperature goes up. The general means of accurate observation is temperature control [30]. In our design, the upward and downward radiation is divided, to yield a spectral albedo for each band.…”
Section: Errors Induced By the Spectral Albedometer Designmentioning
confidence: 99%
See 1 more Smart Citation